Periodontal disease, hypertension and blood pressure among older adults in Puerto Rico - Rivas-Tumanyan, Sona (2012)
BACKGROUND: Current scientific evidence addressing the relation between periodontitis and hypertension is limited to a few studies producing inconsistent results. METHODS: All participants of an on-going representative cohort of Puerto Rican elderly who were 70 years and older and residing in San Juan metropolitan area were invited to this cross-sectional study. Periodontal probing depth (PD) and attachment loss (AL) were summarized using CDC-AAP definition for severe periodontitis (≥2 teeth with AL ≥6mm and ≥1 tooth with PD ≥5mm). We averaged three repeated blood pressure (BP) measurements taken using a standardized auscultatory method. Information on hypertension history, use of anti-hypertensive medications and potential confounders (age, gender, smoking, heavy and binge drinking, diabetes, utilization of preventive dental services, flossing, body mass index, fruit and vegetable, whole wheat bread and high-fiber cereal consumption) was collected during in-person interviews. High BP was defined as average systolic BP ≥140 mmHg or diastolic ≥90 mmHg. Multivariate logistic regression models were used to study the relation between severe periodontitis, hypertension history and high BP. RESULTS: The study population comprised 182 adults. In multivariate analysis, there was no association between severe periodontitis and hypertension history (OR=0.99, 95% CI: 0.40–2.48). Severe periodontitis was associated with high BP, with OR of 2.93 (95% CI: 1.25–6.84), after adjusting for age, gender, smoking, and binge drinking. This association was stronger when restricted to those with hypertension or taking anti-hypertensive medications: OR=4.20 (95% CI: 1.28–13.80). CONCLUSION: Our results suggest that periodontitis may contribute to poor blood pressure control among older adults.